Cultural image of the profession among nursing students - Vieira, Maria Jésia; Cardoso, Normaclei Cisneiros dos Santos (Rev Rene, 2005)
The professional choice was studied in a group of 9 students at the first semester of the Nursing program at the Federal University of Sergipe, the cultural image they had of the profession, the reasons for their choice, their social representations on the profession before the beginning of the course and the experience of the course ‘Nursing Foundations’ as an opportunity for knowing and discussing about the profession. Through the non-structured interview in the beginning of the course, and the questionnaire at the end of it, it can be attested that only 23% of the subjects had Nursing as their first option when taking the vestibular exams, and also lack of information on the profession, and stereotypes. Among the reasons for choosing the Nursing program, the ones who had Nursing as their first option mention liking for the profession, personal aptitude and identification with the help relationship; the ones who had made a different option mention the possibility of passing the vestibular exams, as well as the possibility of using the subject-matters in another major. At the end of the course, 46.8 % of the ones who initially had chosen another major stated that they have identified themselves with the profession, and the ones who chose Nursing as a major stated that they have identified the characteristics of the profession, that they feel more confident and have consolidated the option made.